Medical Healthcare Chatbot - Karani, Mohit; Goyal, Nupur (Journal of Advanced Research in Instrumentation and Control Engineering, 2020)
Regularly Users don't know pretty much all the treatment or manifestations with respect to the specific infection. For little issue client need to go by and by to the medical clinic for registration which is additional tedious. Likewise dealing with the telephonic requires the grumblings is very rushed. Such an issue can be unraveled by utilizing clinical Chatbot by giving legitimate direction in regards to solid living. This paper plans to introduce a structure for a clinical Chatbot that gives analysis and cures dependent on the side effects gave to the framework. The  organisation will  be  able  to amount  the  momentousness  of  the  diagnosis and  if wanted, it will ascribe the user to a doctor obtainable connected.  How to cite this article: Karani M, Goyal N, Agarwal P. Medical Healthcare Chatbot. J Adv Res Instru Control Engg 7(2): 1-3. 2020;